Tactics for Increasing the Effectiveness of Treatment of Oral Changes Caused by Psychotropic Drugs - Kaxxorovna, Raxmonova Baxora (American Journal of Bioscience and Clinical Integrity, 2025)
The results of a study involving 200 people with various diseases of the oral mucosa are presented. A comparative analysis of the clinical results of local treatment of diseases of the mucous membrane, red border of the lips and marginal periodontium with the antiseptic drug Miramistin is presented. In addition, the main aspects of indications and contraindications for the use of the drug by different categories of patients are highlighted. According to the results of the clinical study, Miramistin can be recommended as an effective tool in the complex treatment of diseases of the oral cavity and red border of the lips as part of combination therapy.